Rendering 3D graphics as an aid to stylized line drawings in perspective - Arandjus, Mark; Gabrijelčič Tomc, Helena (Journal of Graphic Engineering and Design, 2016)
The aim of the research was to study the issue of drawing 2D objects and environments in perspective and attempted to ease the process of drawing them with the aid of three-dimensional computer graphics. The goal of the research was to develop the method, which would exclude the need to trace three-dimensional models, which many digital artists use as a guide when making drawings. The need to trace has been eliminated by finding a procedure to render three-dimensional models to appear drawn – to appear drawn by an artist who has a stylized line style. After researching various techniques of rendering, Sketchup was used to make and apply a Sketchup style which emulated a line style. After that, various tests were performed using computer measurements and questionnaires to determine if the observers could distinguish between three-dimensional renders and two-dimensional drawings. The results have shown that very few participants notice three-dimensional graphics rendered with Sketchup. Even among the few observers who did notice the presence of three-dimensional models, none detected even half. The results confirmed the adequateness of the methodology, which enables a more correct creation of element in perspective and convinces the observers that the entire image is stylistically uniform hand drawn image.